Policies for healthy and sustainable edible oil consumption: A stakeholder analysis for Thailand - Bhavani Shankar (2018)
© 2016 The Authors. Objective Palm oil is a cheap and versatile edible oil in widespread use as a food ingredient that has been linked to negative health and environmental outcomes. The current study aimed to understand the prospects for future health-focused policy development to limit food use of palm oil and promote a greater diversity of oils in Thailand's food system. Design Eighteen semi-structured interviews were conducted with a range of stakeholders. The interviews probed views on the economic, health and environmental dimensions of the issue, the prospects for health-focused policy development and the policy development process. Transcripts were analysed using a health policy analytical framework. Setting Thailand. Subjects Stakeholders from a range of ministries, regulatory agencies, the private sector, non-governmental organizations and academia. Results There are several impediments to the emergence of strong regulation, including the primacy of economic considerations in setting policy, doubt and misperception about health implications and a complex regulatory environment with little space for health-related considerations. At the same time, some sections of the food industry producing food for domestic consumption are substituting palm with other oils on the basis of consumer health perceptions. Conclusions Strong regulation to curb the growth of palm oil is unlikely to emerge soon. However, a long-term strategy can be envisaged that relies on greater policy support for other indigenous oils, strategic rebalancing towards the use of palm oil for biofuels and oleochemicals, and harnessing Thailand's food technology capabilities to promote substitution in food production in favour of oils with healthier fatty acid composition.